2013
DOI: 10.1111/1471-0528.12400
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor biometry during a first singleton pregnancy and the relationship with symptoms of pelvic floor disorders: a prospective observational study

Abstract: Objective To assess pelvic floor biometry during pregnancy and the correlation with symptoms of pelvic floor disorders in women.Design A prospective observational study. Setting Antenatal clinic between August 2009 and May 2011.Population Nulliparous women in their first pregnancy.Methods Pelvic floor was assessed by translabial ultrasound and symptoms of pelvic floor disorders were explored with a standardised questionnaire at each trimester.Main outcome measures Pelvic floor biometry during pregnancy.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 33 publications
3
39
2
3
Order By: Relevance
“…Recovery and partial recovery of the pelvic floor structures, such as the bladder neck, within 12 months following childbirth, have been reported previously. Miller et al .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Recovery and partial recovery of the pelvic floor structures, such as the bladder neck, within 12 months following childbirth, have been reported previously. Miller et al .…”
Section: Discussionmentioning
confidence: 56%
“…Recovery and partial recovery of the pelvic floor structures, such as the bladder neck, within 12 months following childbirth, have been reported previously 24,25 . Miller et al 10 reported healing of maternal pubic bone marrow and LAM edema and of subcortical fracture within 8 months after delivery, but found no substantial change in LAM tears.…”
Section: Discussionmentioning
confidence: 80%
“…Strengths of our study include its longitudinal design with nine follow-up timepoints, from 1 day up to 24 weeks postpartum. Another strength is the comparison between hiatal areas postpartum and those at 12 weeks' gestation, and since hiatal area increases as the pregnancy advances 5,6,18 , hiatal dimensions in the first trimester are probably closest to prepregnancy values. Limitations of our study include the small study population and lack of prepregnancy values.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our previous study (21) showed that multiparous women experienced more obvious SUI symptoms and pelvic floor structure changes during pregnancy compared with nulliparous women. However, studies exploring the relation between urinary incontinence during pregnancy and pelvic structure merely took nulliparity into consideration (29,30). In the current study, both nulliparous and multiparous women were investigated, meaning that multiparous women could also be assessed by the nomogram.…”
Section: Discussionmentioning
confidence: 99%